Accuracy and utility of the Structure Sensor for collecting 3D indoor information. Issue 3 (2nd July 2016) - Kalantari, M.; Nechifor, M.
Abstract: This paper presents the result of an investigation into the utility of the Structure Sensor developed by Occipital Inc. and accuracy of its output for 3D surveying of interiors of buildings in relation to Surveying (Cadastral Survey) Regulation 2005 in Victoria, Australia. The paper investigates data acquisition issues, defines guidelines to obtain the best reconstruction result, and evaluates the result against the requirements set by the Regulation. The findings suggest a mixed result. The sensor delivers more accurate outputs for the smaller room sizes. Also, the accuracy does not meet the requirements, but it was found to be close to what is expected in the Regulation. Finally, the paper argues that the device is user-friendly enough to be used by non-experts for crowdsourcing indoor information and, the accuracy of its output can meet the needs of other domains such as indoor navigation and public safety.